Inhibition of mTOR reduces anal carcinogenesis in transgenic mouse model. - Zhi-Jun Sun; Lu Zhang; Wei Zhang; Bradford Hall; Yansong Bian; Ashok B Kulkarni (PLoS ONE)
The molecular mechanism of human anal squamous cell carcinoma (ASCC) is unclear, and the accumulating evidence indicate association of ASCC with the activation of the Akt/mTOR pathway. Here we describe a mouse model with spontaneous anal squamous cell cancer, wherein a combined deletion of Tgfbr1 and Pten in stratified squamous epithelia was induced using inducible K14-Cre. Histopathologic analyses confirmed that 33.3% of the mice showed increased susceptibility to ASCC and precancerous lesions. Biomarker analyses demonstrated that the activation of the Akt pathway in ASCC of the Tgfbr1 and Pten double knockout (2cKO) mouse was similar to that observed in human anal cancer. Chemopreventive experiments using mTOR inhibitor-rapamycin treatment significantly delayed the onset of the ASCC tumors and reduced the tumor burden in 2cKO mice by decreasing the phosphorylation of Akt and S6. This is the first conditional knockout mouse model used for investigating the contributions of viral and cellular factors in anal carcinogenesis without carcinogen-mediated induction, and it would provide a platform for assessing new therapeutic modalities for treating and/or preventing this type of cancer.